Prognostic nutritional index predicts mortality in infective endocarditis - Serkan Kahraman; Hicaz Zencirkıran Aguş; Ali Kemal Kalkan; Fatih Uzun; Mehmet Ertürk; Mehmet Emin Kalkan; Mustafa Yıldız (KARE Publishing, 2020)
Objective: The prognostic nutritional index (PNI), based on serum albumin and lymphocyte concentration, is an inflammation-based nutritional score that has been shown to be a prognostic determinant in several populations. The aim of this study was to investigate the impact of PNI on mortality in patients with infective endocarditis (IE). Methods: A total of 131 patients with IE were enrolled in this retrospective study. The patients were divided into 2 groups based on in-hospital mortality. The PNI value of the patients was evaluated, as well as baseline clinical and demographical variables. Results: Among the study group, 29 patients died in-hospital during the median follow-up of 37 days. The PNI was found to be lower in cases of mortality (35.90+-6.96; 31.09+-5.88; p=0.001). ROC curve analysis also demonstrated that the PNI had a good predictive value for in-hospital mortality with a cut-off value of 35.6 (Area under the curve: 0.691; 95% confidence interval [CI]: 0.589-0.794; p=0.002). In multivariate logistic regression analysis, advanced age (Odds ratio [OR]: 1.078; 95% CI: 1.017-1.143; p=0.012), PNI (OR: 0.911; 95% CI: 0.835-0.993; p=0.034), and leaflet perforation (OR: 5.557; 95% CI: 1.357-22.765; p=0.017) were found to be independent predictors of mortality. Kaplan-Meier survival analysis revealed that long-term survival was found to be significantly decreased in patients with a lower PNI (Log rank: p=0.008). Conclusion: The PNI result was associated with an increased in-hospital mortality rate in patients with IE. The PNI value, advanced age, and cardiac valve perforation as a complication of IE were found to be independent predictors of mortality.